PHYTOPHTHORA PALMIVORA RELATIONSHIP ANALYSIS ON ITS RDNA PRIMERS USING MEGA11 SOFTWARE (NCBI DNA SEQUENCING LIBRARY STUDY) - Yosilia, Rani; Afandi, Auliana; Hoya, Ade Lenty; Cahyani, Christy Nur; Hieno, Ayaka (Jurnal Agrotek Tropika, 2025)
Understanding the genetic relationships of Phytophthora palmivora, a major phytopathogen in tropical crops, is crucial for developing effective management strategies. This study aimed to evaluate the phylogenetic relationships and genetic diversity of P. palmivora using ribosomal DNA internal transcribed spacer (rDNA ITS) and mitochondrial cytochrome oxidase subunit I (COX1) sequences retrieved from the NCBI GenBank database. A total of 61 rDNA ITS sequences and 56 COX1 sequences of P. palmivora, along with one outgroup, were aligned and analyzed using MEGA11 software. The sequences were trimmed and processed using the Kimura-2 parameter model and the Maximum Likelihood method to construct a phylogenetic tree. The results revealed the formation of four major monophyletic clades, indicating clear evolutionary divergence among isolates. The GC content of all sequences was found to be below 50%, suggesting moderate genetic variability, which may influence the adaptability of the species. Environmental factors such as temperature, rainfall, humidity, soil moisture, and seasonal variation were identified as key contributors to the ecological success and distribution of P. palmivora in tropical regions. The integration of ITS and COX1 molecular markers provided complementary insights into the evolutionary history of the species. This study highlights the value of molecular phylogenetics in understanding pathogen diversity and supports future genetic surveillance and breeding programs for disease-resistant crop varieties in tropical agroecosystems.